Regional differences in the distribution of the sub-Saharan, West Eurasian, and South Asian mtDNA lineages in Yemen - Cerný, Viktor; Mulligan, Connie J; Rídl, Jakub; Zaloudková, Martina; Edens, Christopher M; Hájek, Martin; Pereira, Luísa (American journal of physical anthropology, 2008)
Despite its key location for population movements out of and back into Africa, Yemen has not yet been sampled on a regional level for an investigation of sub-Saharan, West Eurasian, and South Asian genetic contributions. In this study, we present mitochondrial DNA (mtDNA) data for regionally distinct Yemeni populations that reveal different distributions of mtDNA lineages. An extensive database of mtDNA sequences from North and East African, Middle Eastern and Indian populations was analyzed to provide a context for the regional Yemeni mtDNA datasets. The groups of western Yemen appear to be most closely related to Middle Eastern and North African populations, while the eastern Yemeni population from Hadramawt is most closely related to East Africa. Furthermore, haplotype matches with Africa are almost exclusively confined to West Eurasian R0a haplogroup in southwestern Yemen, although more sub-Saharan L-type matches appear in more northern Yemeni populations. In fact, Yemeni populations have the highest frequency of R0a haplotypes detected to date, thus Yemen or southern Arabia may be the site of the initial expansion of this haplogroup. Whereas two variants of the sub-Saharan haplogroup M1 were detected only in southwestern Yemen close to the Bab el-Mandeb Strait, different non-African M haplotypes were detected at low frequencies (approximately 2%) in western parts of the country and at a higher frequency (7.5%) in the Hadramawt. We conclude that the Yemeni gene pool is highly stratified both regionally and temporally and that it has received West Eurasian, Northeast African, and South Asian gene flow.
Keywords: Asia; Geography; polymerázová řetězová reakce; DNA, Mitochondrial; Jemen; polymorfismus délky restrikčních fragmentů; Polymerase Chain Reaction; Gene Frequency; lidé; východní Evropa; Mouth Mucosa; Yemen; zeměpis; frekvence genu; Genetic Variation; Africa South of the Sahara; Polymorphism, Restriction Fragment Length; ústní sliznice; Europe, Eastern; mitochondriální DNA; subsaharská Afrika; Asie; genetická variace; Demography; demografie; Humans